Effect of bio fertilization to increase efficiency of using chemical fertilizer to Corn crop (Zea mays L.) grown in gypsiferous soil. - Alkhalifa, khalaf Mahmoud; Almosuly, Mothafer A.; Said, Mazin F. (Journal of Kerbala for Agricultural Sciences, 2018)
A field experiment global was conducted to study the effect of bio fertilization to increase the chemical fertilizer use efficiency for corn crop using bio fertilizer Agrosoil-N of bacteria genus Azotobacter and Agrosoil-P contain Bacillus at levels (without , Azotobacter , Bacillus and both together) with two sources of phosphorus as superphosphate and fine rock phosphate at levels 0 , 42 and 84 Kg P.ha-1 with urea source of nitrogen at levels 0 , 138 and 276 Kg N.ha-1. Potassium sulphate fertilizer was applied for all treatments at one level of 120 Kg K2O.ha-1. The experiment was conducted using RCBD with three replicates. Means were tested with (L.S.D) at 5% . Results showed that the application of bio fertilizer as single and dual inoculation for two sources phosphate significant increases of all studied parameters were increasing highed in dual inoculation. Combination of bio fertilizer with 42 Kg P.ha-1 recorded plant height 179,94 cm , leaf area 501.85 cm2 and grain yield 7.421 ton. ha-1 and this dose not differ significant of 84 Kg P.ha-1without inoculation. This interaction gave increasing of N , P and K in grain 54,43% , 169.93% and 15.60% respectively . The dual inoculation with 42 Kg P.ha-1 super phosphate and 84 Kg P.ha-1 rock phosphate higher means in Fe , Zn concentration gave 107.40 , 57.24 and 101.46 , 55.347 ppm in grain was significant of recommended without inoculation . The interaction between dual inoculation with 42 Kg P.ha-1 recommended dose exhibited the highest values of chemical fertilizer using efficiency 19.45 Kg grain for each one kilogram chemical fertilizer added.